Student Management Strategies and Their Impact on School Discipline: A Systematic Review - Nurussalamah; Yetri; Oki Dermawan (Al-Qalam Institue, 2026)
This study aims to examine the role of student management in enhancing student discipline across various educational settings. A literature review method was employed by analyzing and synthesizing findings from 15 recent scholarly articles related to student management and disciplinary practices, with a focus on identifying key management strategies, supporting factors, and challenges influencing the development of student discipline. The findings indicate that effective student management contributes significantly to improving discipline through structured planning, student participation, orientation programs, and engagement in extracurricular activities. The study also reveals that leadership, positive role models, supportive school culture, and parental involvement are critical factors in fostering disciplined behavior. However, limited resources, diverse student backgrounds, and low levels of student participation may reduce the effectiveness of discipline-related initiatives. The implications of this study suggest that educational institutions should adopt a multidimensional approach that integrates clear regulations, active student involvement, and continuous monitoring to strengthen both behavioral and academic outcomes. Furthermore, enhancing student engagement in governance and decision-making processes may support the sustainability of disciplinary improvements. Future studies are encouraged to conduct comparative analyses across educational contexts and explore innovative strategies for increasing student participation.